2013
DOI: 10.1111/ijac.12061
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Anisotropic Properties of Textured ZrB2 and ZrB2MoSi2 Ceramics Prepared by Strong Magnetic Field Alignment

Abstract: Dense, highly textured ZrB2 and ZrB2–MoSi2 ceramics were fabricated via a strong magnetic field alignment method followed by spark plasma sintering. Unlike with the previous studies, which only focused on the alignment of single‐phase particles, both ZrB2 and MoSi2, which exhibited a magnetic anisotropy, have been aligned in this study. The alignment of MoSi2 in the same direction of ZrB2 enhanced the degree of orientation of ZrB2, decreased the grain size, but increased the aspect ratio of the platelet ZrB2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…For texturing ZrB 2 , the optimized suspension parameters for slip casting were determined as 20 vol% ZrB 2 and 1.5 wt% polyethyleneimine (PEI) dispersant of powder in the ethanol or in water, which contributed to the low viscosity of suspension. It was confirmed that the c -axis of ZrB 2 particles was parallel to the 12 T magnetic field direction [14, 16]. …”
Section: Introductionmentioning
confidence: 98%
“…For texturing ZrB 2 , the optimized suspension parameters for slip casting were determined as 20 vol% ZrB 2 and 1.5 wt% polyethyleneimine (PEI) dispersant of powder in the ethanol or in water, which contributed to the low viscosity of suspension. It was confirmed that the c -axis of ZrB 2 particles was parallel to the 12 T magnetic field direction [14, 16]. …”
Section: Introductionmentioning
confidence: 98%
“…51,52,60 As applied to hot pressing and SPS of ZrB 2 powders, attempts were undertaken to replace initial random distribution of particles by certain ordered patterns using colloidal processing, 61 texturing by slip casting 62 and magnetic texturing. 63 After slip casting, extended zirconium diboride particles (2 ± 5 mm in diameter and 10 ± 25 mm long) are hot pressed at 2000 8C at a pressure of 30 MPa. 62 A magnetic field of 12 T was also used for texturing ZrB 2 and ZrB 2 + MoSi 2 samples.…”
Section: Ii2 Preparation Of Consolidated Nano-and Micromaterialsmentioning
confidence: 99%
“…62 A magnetic field of 12 T was also used for texturing ZrB 2 and ZrB 2 + MoSi 2 samples. 63 At present, methods for consolidation of boride nanopowders (see above) do not provide a complete retention of nanostructure; additional search for optimum conditions are required.…”
Section: Ii2 Preparation Of Consolidated Nano-and Micromaterialsmentioning
confidence: 99%
“…Zirconium diboride finds applications as high temperature electrode and nose of hypersonic aircrafts due to its high melting point (3250°C), high thermal conductivity (55 W/(m·K)), and high flexural strength (536 MPa) . Generally, to enhance its fracture toughness and accelerate densification, SiC is added .…”
Section: Introductionmentioning
confidence: 99%
“…The composites showed anisotropic mechanical properties resulting in an enhancement along a particular direction. Especially, the oxidation resistance was greatly enhanced along the c ‐axis direction …”
Section: Introductionmentioning
confidence: 99%